GIS Smart Mapping Technique For Urban Spatial Pattern Analysis - A Case Study On Nibong Tebal Sub-District - Ahmad, Ramlah (Universiti Sains Malaysia, 2005)
This study developed and validate a new fast, cost-benefit technique of mapping and monitoring urban land cover characteristics using high resolution satellite sensor images integrated with digital ‘framework’ of GIS data. This technique has successfully determined the extent of the urban land cover changes in Nibong Tebal sub-district by means of GIS spatial pattern analysis study. The research covers several stages of work including pre-research, literature review, database development, data collection, system software application, data entry stage, data analysis and data output stage. There are five methods of spatial analysis that have been carried out, namely resampling, classification, raster-vector conversion, image cross-tabulation, and spatial pattern analysis in analyzing and detecting the urban land cover changes. The results showed that there are changes in the built-up/urban area and were very significant due to the expansion of the residential and commercial area. The result also indicated the decrease of the agricultural area such as oil palm and rubber plantations due to the rapid urban expansion. Other results obtained in this study showed some minor changes in the river outline probably due to the errosion and the increase of sub-district roads over the areas. In conclusion, this research provides useful results in demonstrating a process of integrating information derived from satellite imagery with other spatial data in land use change detection study.